A virtuous cycle in materials engineering and surface finishing: design-print-image. (3rd March 2020) - Walsh, F. C.; Arenas, L. F.; Ponce de León, C.
ABSTRACT: Electrochemical cells continue to be important in the synthesis and processing of commodity and speciality chemicals, environmental remediation, energy conversion and electrodeposition. A current challenge is an increasing need to achieve a high performance from cells which can be easily designed, manufactured or modified. Conventional manufacturing has involved machining of cast and extruded materials in a mechanical engineering workshop, which can involve delays, the need for skilled specialists and considerable costs. Increasingly, the benefits of fast prototyping as a route to manufacture are being realised. Modern approaches to detailed imaging of structures (e.g. by computed tomography) can be combined with on-screen, digital design ( via computer software suites), followed by modification then data export to a 3D printer. In this fashion, a fast, flexible, cost effective and attractive route to manufacture of prototype electrodes and cell bodies can be realised. This review paper demonstrates the success of a design-image-manufacture cycle to realise polymeric electrochemical flow cell compartments and electrodes. Future developments are suggested, with 3D printing likely to offer creative solutions in many surface finishing applications.